Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS Melalui Pendekatan Teaching at The Right Level (TaRL) di Kelas V SDN 101766 Bandar Setia - Harahap, Febriza Wirahma Dina; Harahap, Yulia Sari; Pasaribu, Arda Yatul Liani; Nurhafni, Nurhafni; Sari, Wulan Tahnia (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to find out how the Teaching at The Right Level (TaRL) approach can be used to improve the learning outcomes of social studies for grade V students of SDN 101766 Bandar Setia in the 2024-2025 school year. This research is a Class Action Research (PTK). This research was conducted for two semesters. Each series consists of four steps: observation, reflection, implementation of actions and planning. The subjects of this study are 24 students and teachers in grade V of SDN 101766 Bandar Setia which totals 24 people. Data collection was carried out by observation, questionnaires, documentation and interviews. The resulting data was analyzed descriptively consisting of: data reduction, data analysis, and sentiment analysis. This study proves that there is an increase in the percentage of students who achieve the Minimum Completeness Criteria (KKM) before and after the intervention. The average class score in the pre-cycle was 59.58, increasing to 72.70 in the first cycle, and reaching 87.08 in the second cycle.